Parents' perspectives on adopting English names in Taiwan. Issue 8 (16th November 2016) - Huang, Chiu-Yen; Ke, I-Chung
ABSTRACT: This study investigated the adoption of English names in Taiwan through questionnaires and interviews with parents of junior high school students. In total, 564 parents filled out a questionnaire regarding their adoption of an English name, reasons for needing an English name, and their perspectives about their child's English name. We interviewed nine parents with different answers in the questionnaire to explore parents' perceptions of English names. The results revealed that 59% had or used to have an English name. Those with a higher level of education were more likely to have an English name. The two most common reasons for adopting an English name were attending English lessons and satisfying an occupational requirement. Regarding their children, 89% had an English name, and 96% of these children acquired it before they were enrolled in junior high school. The findings imply that an English name has gradually become a component of a glocal identity in Taiwan and this may have wide implications.